Association between total dietary choline intake and lumbar spine bone mineral density in postmenopausal women based on NHANES 2007–2018 - Jincheng Bai; Penghui Lv; Lu Li; Sichao Cheng; Jianjun Chang (Scientific Reports)
Abstract Postmenopausal estrogen deficiency accelerates bone mineral density (BMD) decline, significantly elevating the risk of osteoporotic fractures. Choline, a vital nutrient involved in lipid homeostasis and inflammatory pathways, has been associated with skeletal health. Yet its role in preserving bone density among postmenopausal populations, a group at high risk of osteoporosis, requires further investigation. This study also examined the modifying effects of socioeconomic factors, including income and race, on the relationship between dietary choline intake and BMD. Using data from 4,160 postmenopausal women aged 50 years and older from the National Health and Nutrition Examination Survey (NHANES) 2007–2018, we employed weighted linear regression models to characterize the dose-response relationship between total dietary choline intake and lumbar spine BMD. In fully adjusted models, each 1 g/day increment in choline intake corresponded to a 0.082 g/cm² increase in lumbar spine BMD (β: 0.082, 95% CI: 0.025–0.139). Participants in the highest choline intake quartile (Q4) exhibited a 0.025 g/cm² higher BMD compared to the lowest quartile (Q1) (β: 0.025, 95% CI: (0.007, 0.042)). Stratified analyses revealed significant effect modifications by obesity (P interaction = 0.015), income (P interaction = 0.003), and race (P interaction = 0.039), with amplified protective effects observed in obese individuals (β: 0.146, 95% CI: 0.067–0.22), high-income subgroups (PIR > 4)(β: 0.121, 95% CI: 0.013–0.228), and non-Hispanic Whites (β: 0.110, 95% CI: 0.034–0.185). This study demonstrates for the first time the positive association of dietary choline with BMD in postmenopausal women, supporting the potential of choline-targeted nutrition strategies for osteoporosis prevention and emphasizing the role of socioeconomic factors in influencing bone health outcomes.